Rheological and chemical characteristics of rubberized binders with non-foaming warm mix additives. (15th May 2016) - Yu, Huayang; Leng, Zhen; Xiao, Feipeng; Gao, Zheming
Highlights: Various selected WMA additives had similar effects on AR's workability. Various selected WMA additives had different effects on AR's rheological properties. Using Evotherm-DAT and Sasobit together compromised the engineering performance of AR. Rubber compensated adverse effect of wax on low-temperature performance of asphalt. Incorporation of WMA additives affected the dissolution of crumb rubber in asphalt. Abstract: This study aims to investigate the rheological and chemical characteristics of asphalt rubber (AR) binders modified with four non-foaming warm mix asphalt (WMA) additives: Evotherm-DAT, Sasobit, conventional paraffin wax, and combined Evotherm-DAT and Sasobit. The main findings of this study include that: (1) all selected WMA additives are effective in enhancing AR's workability; (2) using combined Evotherm-DAT and Sasobit is not a viable option to reduce the construction temperature of AR mixture; (3) paraffin wax is a potential WMA additive for AR; and (4) WMA additives may affect the dissolution status of crumb rubber in base asphalt.